2016
DOI: 10.1007/s00198-016-3735-z
|View full text |Cite
|
Sign up to set email alerts
|

Three doses of vitamin D, bone mineral density, and geometry in older women during modest weight control in a 1-year randomized controlled trial

Abstract: The decline in Ct thickness was prevented with higher vitamin D supplementation, but there were no other significant changes due to treatment over 1 year. Whether these findings translate to changes in biomechanical properties leading to reduced fracture risk should be addressed in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 52 publications
1
39
0
Order By: Relevance
“…Although the primary outcome of the trial was to assess the influence of a Mg diet strategy on vitamin D status in postmenopausal women, the sample size in each group would allow us to preliminarily obtain significant results, although the results should be carefully considered. Clinical trials of the same nature and a similar sample size have shown a positive effect of different interventions on some parameters status in postmenopausal women [54][55][56]. Likewise, the sample size limitation did not allow us to make a more complex statistical approach since we did not have enough power to perform multivariate analyses and to be able to adjust our model based on possible confounding variables such as previously described age or BMI.…”
Section: Discussionmentioning
confidence: 98%
“…Although the primary outcome of the trial was to assess the influence of a Mg diet strategy on vitamin D status in postmenopausal women, the sample size in each group would allow us to preliminarily obtain significant results, although the results should be carefully considered. Clinical trials of the same nature and a similar sample size have shown a positive effect of different interventions on some parameters status in postmenopausal women [54][55][56]. Likewise, the sample size limitation did not allow us to make a more complex statistical approach since we did not have enough power to perform multivariate analyses and to be able to adjust our model based on possible confounding variables such as previously described age or BMI.…”
Section: Discussionmentioning
confidence: 98%
“…One-year, randomized, double-blind controlled study examined the influence of vitamin D in healthy obese older women on the density and quality of bone in fifty eight elderly women surveyed. The decline in the thickness of the cortical width of the tibia was prevented by the treatment of higher doses of vitamin D, but there were no other significant changes caused by the treatment over a period of one year [12].…”
Section: Nutrition and Health Of Elderly Peoplementioning
confidence: 88%
“…Consistent with a meta‐analysis of RCTs that showed a significantly inferior effect of higher‐dose vitamin D supplementation on aBMD in the lumbar spine compared with lower‐dose vitamin D supplementation, Mendelian randomization analyses have found a possible inverse relation of vitamin D status with skeletal health . Consequently, the possibility of a causal positive association between serum 25(OH)D levels and aBMD would be almost ruled out by these two key analyses to assess causality, though the indirect effects of high‐dose vitamin D supplements in RCTs could be detected in the hip or tibia . Accordingly, the positive linear correlation between serum 25(OH)D levels at 12 months and change in aBMD in the lumbar spine can be interpreted as a result of the involvement of individual life and health status including physical activity outdoors because the wide variability in serum 25(OH)D levels after supplementation with vitamin D suggests that serum 25(OH)D levels at 12 months resulted not only from vitamin D supplements, but also from other factors such as vitamin D synthesis in the skin following sunlight exposure.…”
mentioning
confidence: 88%